Effects of deuteration on the structure and magnetic properties of bis-quinolinium tetrabromidocuprate(II) dihydrate. Issue 22 (17th December 2019) - Monroe, Jeffrey C.; Landee, Christopher P.; Turnbull, Mark M.; Wikaira, Jan L.
Abstract: The partially [d6, 2 ] and fully [d20, 3 ] deuterated analogues of (QuinH)2 CuBr4 ·2H2 O (d0, 1 ) were prepared and their crystal structures were determined [Quin = quinoline]. In both compounds, there is a clear disorder in the positions of the bromide ions which was resolved. This led to a reexamination of the structure of the parent, fully protonated compound (1 ) where a small percentage of previously unrecognized disorder was also observed and the structure rerefined. Variable temperature magnetization measurements over the range 1.8–310 K indicate that all three materials behave as magnetically well-isolated layers that can be evaluated using the 2D-quantum Heisenberg antiferromagnetic model. Final fitting results for the partially ( J = −5.96(5) K) and fully ( J = −5.77(2) K) deuterated compounds indicate slightly weaker exchange compared to the protonated compound ( J = −6.17(3) K), likely as a result of the increased disorder in the deuterated phases. Graphical Abstract: